The Simulation Analysis of Optimal Policy Including Introduction of Biomass Plant Technology for Decreasing Water Pollutions in Jiaxing City, China - Yoshiro Higano; Feng Xu; Jingjing Yan; Takeshi Mizunoya; Huanzheng Du (European Regional Science Association (ERSA), 2010)
In the study, we proposed the environmental policies to decrease water pollutants that generate from household, non-point and production in Jiaxing city of China. We especially introduced biomass plant technology for pig farming industry in order to improve the water environment. We constructed environmental model and social economic model by computer simulation that evaluated the efficiency of biomass plant technology from both water environmental preservation and social economic development. The research established the significance and feasibility of introducing biomass plant technology that allows simultaneous pursuit of environmental improvement and regional development. The comprehensive evaluation and optimal policies are expected to form the basis of decision-making in Jiaxing city.
Keywords: 330; Biomass plant; Environmental policy; Simulation; Model